2003
DOI: 10.1002/art.11357
|View full text |Cite
|
Sign up to set email alerts
|

Successful tumor necrosis factor α blockade treatment in therapy‐resistant sarcoidosis

Abstract: Sarcoidosis is a multisystemic disorder histologically characterized by a noncaseating granulomatous inflammatory process. The etiology remains unclear, but tumor necrosis factor ␣ seems to play a crucial role. Herein we describe a patient with severe sarcoidosis involving the lung and liver. Various treatment regimens with azathioprine, methotrexate, cyclophosphamide, and pentoxifylline failed to control the disease. Therefore, salvage therapy with infliximab was commenced. Arthritis and pulmonary and liver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 5 publications
2
33
0
2
Order By: Relevance
“…The results of our study are in line with other case series demonstrating efficacy of infliximab in 64-100% of sarcoidosis patients treated [12,30,31]. In the present study, uveitis demonstrated the best response rate (74%), followed by RFI (57%) and SFN (54%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are in line with other case series demonstrating efficacy of infliximab in 64-100% of sarcoidosis patients treated [12,30,31]. In the present study, uveitis demonstrated the best response rate (74%), followed by RFI (57%) and SFN (54%).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, uveitis demonstrated the best response rate (74%), followed by RFI (57%) and SFN (54%). These response rates are in line with previous research [11,23,29,31,32]. It is probable that the higher response rate for uveitis is influenced by the shorter time between diagnosis and initiating TNF inhibitors (4.5¡4.3 years for uveitis, compared with 6.3¡5.6 years for SFN and 6.8¡5.6 years for RFI; p50.05).…”
Section: Discussionsupporting
confidence: 90%
“…The choice of agent therefore depends on other factors, including individual symptoms, patients' convenience, access to treatment and patients' preferences [7]. But TNFalpha inhibition has also been associated with induction or worsening of various autoimmune diseases, such as systemic lupus, vasculitis, interstitial lung disease, psoriasis, and the granulomatosis Crohn's disease and also sarcoidosis.…”
Section: Discussionmentioning
confidence: 98%
“…[83][84][85][86][87][88][89][90] Table 7 summarizes the use of infl iximab for lung disease, including four RCTs for lung disease 86,89,91,92 and 11 case series of infl iximab in which additional information regarding toxicity is provided. 85,[93][94][95][96][97][98][99][100][101][102] Also included in Table 8 are several studies in nonpulmonary disease that provide specifi c information regarding toxicity of the drug. 10,76, 3.1.3.1 Toxicity-Detailed reviews of the side effect profi le have been published.…”
Section: Infl Iximabmentioning
confidence: 99%